Morphological evaluation of zygomatic root of sapajus apella primates - Ferreira, Maria; Rossi, Ana; Freire, Alexandre; Araujo, Rafael; Botacin, Paulo; Prado, Felippe (Revista dos Trabalhos de Iniciação Científica da UNICAMP, 2019)
The aim of this study was to evaluate the position of the maxillary premolars and molars in relation to the zygomatic alveolar crest of Sapajus apella monkeys. The results suggested that there are differences in position between the premolars and molars in relation to the long axis of the zygomatic alveolar crest of Sapajus apella monkeys. The third premolar is the one closest to the long axis of the zygomatic alveolar ridge.